STUDI LITERATUR : PENGARUH KUALITAS FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI LIU’S NELAYAN DI CEMARA ASRI MEDAN - Devi Adinda Putri; Mutiara Sani; Najwa Athanya; Irnawati Irnawati; Agus Rahmadsyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of facility quality and service quality on customer satisfaction at Liu's Nelayan Cemara Asri Medan restaurant. As one of the leading restaurants in the region, Liu's Fisherman faces the challenge of maintaining and increasing customer satisfaction levels amidst increasingly fierce competition. This research uses quantitative methods by collecting data through questionnaires distributed to restaurant customers. Data analysis was carried out using multiple linear regression to test the influence of the independent variables, namely facility quality and service quality, on the dependent variable, namely customer satisfaction. The research results show that facility quality and service quality have a significant influence on customer satisfaction. The quality of facilities including comfort, cleanliness and restaurant aesthetics makes a positive contribution to the customer's dining experience. Apart from that, service quality which includes friendliness, speed and professionalism of staff is also a main factor that increases customer satisfaction. Thus, improving the quality of facilities and services is recommended to maintain customer loyalty and restaurant competitiveness.